1994
DOI: 10.1002/jmor.1052200206
|View full text |Cite
|
Sign up to set email alerts
|

Follicular placenta of the viviparous fish, Heterandria formosa: II. Ultrastructure and development of the follicular epithelium

Abstract: Embryos of the viviparous poeciliid fish, Heterandria formosa, develop to term in the ovarian follicle where they undergo a 3,900% increase in embryonic dry weight. Maternal-embryonic nutrient transfer occurs across a follicular placenta that is formed by close apposition of the embryonic surface (i.e., the entire body surface during early gestation and the pericardial amnionserosa during mid-late gestation) to the follicular epithelium. To complement our recent study of the embryonic component of the follicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 38 publications
7
73
0
2
Order By: Relevance
“…The finding of maternal metal transfer in H. formosa was not surprising, since it is considered a matrotrophic species (Grove and Wourms 1994;Uribe and Grier 2011). We would not expect differences in metal levels among first-brood offspring from exposed and control females if G. affinis were fully lecitotrophic (i.e.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The finding of maternal metal transfer in H. formosa was not surprising, since it is considered a matrotrophic species (Grove and Wourms 1994;Uribe and Grier 2011). We would not expect differences in metal levels among first-brood offspring from exposed and control females if G. affinis were fully lecitotrophic (i.e.…”
Section: Discussionmentioning
confidence: 78%
“…Heterandria formosa is a species with specialized matrotrophy; a provisioning mode in which the female continues to transfer provisions to the embryo during development (Grove and Wourms 1994;Wourms et al 1988;Uribe and Grier 2011). Furthermore, this species exhibits superfetation, which is the simultaneous development of multiple broods at different developmental stages (Marsh-Matthews 2011;Pires et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…In the inner layer, we identified numerous vesicles, microvilli on the apical surface (zone closest to the embryonic tissue), cell junctions and extensive endoplasmic reticulum. An additional characteristic we noticed was the presence of a follicular ribbon or egg envelope (porous fertilization membrane), which was observed in some species of the genera Heterandria and Poeciliopsis (Heterandria formosa, Poeciliopsis gracilis, P. latidens, P. occidentalis, P. turrubarensis and P. viriosa; Grove & Wourms, 1994;Kwan et al, 2015). We can conclude that the inner follicular layer in all species has a high degree of metabolic activity and is responsible for the transfer of nutrients from the mother to the embryo.…”
Section: Discussionmentioning
confidence: 83%
“…To date, this is the only study that has examined the relationship between degree of matrotrophy and placental complexity, even though many studies have assumed that higher degrees of matrotrophy require more complex placentas (Ostrovsky et al, 2016;Pollux et al, 2014;Reznick, Mateos, & Springer, 2002). The hypothesis is that females that transfer more nutrients to their embryos during development (i.e., more matrotrophic species) require a more complex placenta (Grove & Wourms, 1994;Jollie & Jollie, 1964;Kwan et al, 2015;Turner, 1940). Therefore, one of the main objectives of this study was to analyse whether there is a relationship between degree of matrotrophy and several ultrastructural characteristics of the maternal follicular placenta.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated impressively that the embryo-allograft within the follicle was isolated from maternal immune rejection. Tight junctions have been described connecting cells of the follicular epithelium in Heterandria formosa (Grove and Wourms, 1994) and in Poecilia reticulata (Jollie and Jollie, 1964). Here, as in the luminal walls of the ovary, tight junctions are believed to produce an effective barrier preventing the movement of molecular and cellular agents of maternal immune rejection to the embryo.…”
Section: ) During Insemination Inmentioning
confidence: 99%